Nilai Religius pada Puisi Sujud Karya K.H. Ahmad Mustofa Bisri - Sari, Siska Amelia; Rafifah, Jihan; Febriana, Vina (Literature Research Journal, 2023)
This study aims to describe the religious value contained in the poem Sujud by K.H. Ahmad Mustofa Bisri through a literary semiotic approach. The method used is a qualitative descriptive method. The source of this research data is an elegy poem by K H. Ahmad Mustofa Bisri entitled "Sujud". While in the data is the religious value contained in the poem Sujud by K.H. Ahmad Mustofa Bisri. The data collection of this study used the listen method which was carried out with record and read techniques. The result in this analysis of religious values should be that we as human beings should be kind, should not feel more or want to usurp the rights of others. In the world only for a moment multiply worship by kowtow to God we do not forget where we came from. In addition, in this analysis found 3 types of religious values, namely Priestly Tawhid, Religious Morals, and Religious WorshipPenelitian ini bertujuan untuk mendeskripsikan nilai religius yang terkandung dalam puisi Sujud karya K.H. Ahmad Mustofa Bisri melalui pendekatan semiotik sastra. Metode yang digunakan yaitu metode deskriptif kualitatif. Sumber data penelitian ini adalah puisi elegi karya K H. Ahmad Mustofa Bisri yang berjudul "Sujud". Sedangkan dalam datanya adalah nilai religius yang terkandung dalam puisi Sujud karya K.H. Ahmad Mustofa Bisri. Pengumpulan data penelitian ini menggunakan metode simak yang dilakukan dengan teknik catat dan baca. Hasil dalam analisis nilai religius ini hendaknya kita sebagai manusia harus bersikap baik, tidak boleh merasa lebih ataupun ingin merebut hak orang lain. Di dunia hanya sesaat perbanyak ibadah dengan bersujud kepada Allah kita tidak lupa dari mana kita berasal. Selain itu, dalam analisis ini ditemukan 3 jenis nilai religius, yakni Keimaman Tauhid, Keagamaan Akhlak, dan Keagamaan Ibadah.